Recent Advances and Future Prospects in Knowledge, Information and Creativity Support Systems Selected Revised Papers from the Tenth International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2015), 12-14 November 2015, Phuket, Thailand - Theeramunkong, Thanaruk; Skulimowski, Andrzej M.J; Yuizono, Takaya; Kunifuji, Susumu (Advances in Intelligent Systems and Computing, 2018)
This book includes carefully selected papers presented at the 10th International Conference on Knowledge, Information and Creativity Support Systems (KICCS 2015), which was held in Phuket, Thailand, on November 12-14, 2015. Most of the papers are extended versions with the latest results added, representing virtually all topics covered by the conference. The KICCS 2015 focus theme, "Looking into the Future of Creativity and Decision Support Systems", highlighted the field's growing complexity and called for deeper, insightful discussions about the future, complemented with an exposition of current developments that have proven their value and usefulness. As such, the book addresses topics concerning future-oriented fields of research, such as anticipatory networks and systems; foresight support systems; and relevant newly emerging applications, exemplified by autonomous creative systems. It also focuses on cognitive and collaborative aspects of creativity.